?ApPLICATION OF COMMERCIAL SANITIZERS IN CHICKEN HOUSES PART L GROWTH AND MEAT QUALITY (Biological Sciences - PJSIR, 2000)
Four disinfectants employed as sanitizer in the chicken houses were TH4, Prophyl, Beloran and Fourtedes. This phased study was completed in 45 days. The stimulating effect showed considerable variability in all the [our disinfectants. The mean values offeed conversion ratios of the experimental groups were better than the control group. Gross pathological study of trachea, lungs and liver was also carried out. Application of all the four sanitizers was found to be safe as no toxic effects were recorded. Chemical analysis of meat derived from these chickens showed non significant variations within a narrow range. Except for the fat and moisture content the parameters other tested showed nonsignificant differences (P>O.05).